Efficient predictive algorithms for image compression. (2017) - Lucas, Luís Filipe Rosário; Rodrigues, Nuno Miguel Morais; Pagliari, Carla Liberal; Da Silva, Eduardo A. B (Eduardo Antônio Barros), 1963-; Faira, Sérgio Manuel Maciel de
No abstract available